(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
Graph theory is a fastly developing area of mathematics and is present in our everyday life. The internet and navigation systems can be modelled with graphs as well as the connection of braincells or human connections. In Hungary in 1984. graph theory was not part of the curriciula for math teacher students, now it is a part of the highschool final exam. In our work we propose a way to teach graph theory in highschool. We planned a material based on the suggestions of researchers of the area. We tought the material in grade 9 and as a verification we put together a test for these pupils consisting of the final exam problems.